The Role of Toll-Like Receptors in Autoimmune Diseases through Failure of the Self-Recognition Mechanism - Mark Farrugia; Byron Baron (International Journal of Inflammation)
Toll-like receptors (TLRs), part of the innate immune system that recognises molecular signatures, are important in the recognition of pathogenic components. However, when specific cellular contexts develop in which TLRs are inappropriately activated by self-components, this may lead to sterile inflammation and result in the occurrence of autoimmunity. This review analyses the available data regarding TLR biochemistry, the specific mechanisms which are brought about by TLR activation, and the importance of these mechanisms in the light of any existing and potential therapies in the field of autoimmunity.